Photochemistry of Tris(2, 4‐dibromophenyl)amine and its Application to Co‐oxidation on Sulfides and Phosphines. (8th March 2021) - Bonesi, Sergio M.; Mella, Mariella; Merli, Daniele; Protti, Stefano
Abstract: The photochemistry of tris(2, 4‐dibromophenyl)amine was investigated via time‐resolved nanosecond spectroscopy. The tris(2, 4‐dibromophenyl)amine radical cation ("Magic Green") was immediately detected after the laser pulse; this intermediate then cyclizes to N ‐aryl‐4a, 4b‐dihydrocarbazole radical cation. The latter transient reacted with molecular oxygen to provide the corresponding hydroperoxyl radical, which smoothly co‐oxidize sulfides into sulfoxides. On the other hand, the photogenerated "Magic Green" was exploited to promote the co‐oxidation of nucleophilic triarylphosphines to triarylphosphine oxides through an electron transfer process preventing the amine cyclization. In this case, the intermediate Ar3 POO + was found to play a key role in phosphine oxide formation. Abstract : The photochemistry of tris(2, 4‐dibromophenyl)amine was investigated via time‐resolved nanosecond spectroscopy. Two transients were immediately detected after the laser pulse, viz. the tris(2, 4‐dibromophenyl)amine radical cation (the so‐called "Magic Green") and the N ‐aryl‐4a, 4b‐dihydrocarbazole radical cation. The latter species reacted with molecular oxygen and smoothly co‐oxidizes sulfides into sulfoxides. On the other hand, the photogenerated "Magic Green" promoted the co‐oxidation of nucleophilic triarylphosphines to triarylphosphine oxides via electron transfer preventing the triarylamine cyclization. In this case, the intermediate Ar3 POO + was found to play a key role in phosphine oxide formation.